PROGRAM PAWON URIP SEBAGAI UPAYA MEMENUHI KEBUTUHAN POKOK PASCA PANDEMI DESA DAWUHAN WETAN - Andi Wapa; Wijaksono, Agus (Jurnal Pengabdian dan Pemberdayaan Banyuwangi (Jurnal Abdiwangi), 2023)
Pawon Urip is a cultivation carried out by the Dawuhan Wetan community to overcome the post-pandemic problems that hit Indonesia. Pawon Urip consists of a type of vegetable vegetable plant that can be applied directly by the local community. Methods used in implementing the program include qualitative and quantitative data collection methods that involve observation and outreach to the oppressed population. The results of its development have overall developed very well in accordance with the expected plans. There are 7 types of plants used, including: spinach, kale, chilies, eggplant, mustard greens, and lemongrass. Pawon Urip was formed to increase the creativity and independence of residents who take part in this service
Keywords: Pawon urip; Creativity; Independence; plant